Effectiveness of low-dose aspirin in reducing the risk of preeclampsia in women with chronic hypertension: an integrative literature review - Prisca Asiimwe; Grace Nambozi; Laura Brennaman; Joseph Ngonzi; Gad Ruzaaza (BMC Cardiovascular Disorders, 2025)
Background: Evidence on the use of aspirin in women with chronic hypertension has indicated low effectiveness in preventing superimposed preeclampsia. The possible cause has not been well explored. Many researchers have attributed it to inadequacies in dosages, timing of therapy initiation, timing of intake and adherence. Investigations into these aspects have yielded conflicting results. Previous research has mainly focused on the dosage and gestational timing, yet the timing the drug is taken and adherence are also important aspects in evaluating drug efficacy. Therefore, an appraisal of the combination of these parameters was necessary. Aim: This review aimed to explore the theoretical explanations for aspirin's low effectiveness in reducing the incidence of superimposed preeclampsia among women with chronic hypertension and propose therapy modifications to boost aspirin. We also aimed to synthesize evidence on the effectiveness of aspirin at different doses, gestation timing, timing of ingestion, and adherence in this population. Methods: The review followed the Whittemore and Knafl procedure which involves problem identification, literature search, data extraction/evaluation, data analysis and presentation of findings. 17 studies were evaluated in the integrative literature review obtained from international databases including PubMed, Hinari and Google Scholar. We searched for articles that pertained to the effectiveness of aspirin regarding dosage, gestational age at initiation, timing of ingestion and adherence. Results: On exploration of the possible explanation for the low effectiveness of aspirin on superimposed preeclampsia, it was noted that the pathogenesis of this condition in chronic hypertension has various pathways. However, aspirin targets only one of them, thereby leaving a gap for the other pathways to advance. After synthesizing the studies included in this review, it was noted that aspirin doses≥150 mg were safer and more effective in the majority of the populations. Overall, there was an optimistic trend between higher doses (≥150 mg), initiated before 12 weeks of gestation, taken over 90% of the time at night/bedtime. Conclusion: Owing to the variety of pathways through which preeclampsia develops in women with preexisting hypertension, this review recommends weight-adjusted multi-component pharmacological combinations such as aspirin and L-arginine, or aspirin and S-nitroglutathione to enhance aspirin’s effectiveness in this population. We also noted that the effectiveness of aspirin largely depends on early identification and control of hypertension,doses≥150 mg, initiation of the therapy before the 12th week of gestation and taking the drug more than 90% of the time at night/bedtime. We recommend further research in this area, consistent follow-up of women prescribed aspirin and use of combined methods to measure adherence.
Keywords: Preeclampsia; Superimposed preeclampsia; Effectiveness aspirin and superimposed preeclampsia; Efficacy aspirin prophylaxis; Chronic hypertension during pregnancy